Dissecting the impact of chimeric antigen receptor expression levels on T cell behaviour and response - Ramos, AS (2022)
Chimeric antigen receptor (CAR) T cells have heralded in a new age in cancer treatment. CAR T therapy has demonstrated remarkable responses in cancer patients of blood cancers. The therapy's success lies in the expression of a chimeric antigen receptor (CAR) that reprograms and redirects T cells to specifically target and attack cancer cells. However, CAR T therapy has faced numerous challenges with attempts to translate this success into solid cancers. Issues related to on-target, off-tumour toxicity, tonic signalling, and T cell dysfunction have limited numerous efforts. However, recent evidence demonstrated that CAR expression levels are a critical determinant in T cell activity and therapeutic efficacy – even more so in mediating T cell exhaustion. While insightful, this work assesses only two levels of CAR expression. Thus, there is a notable, outstanding gap in thoroughly understanding how CAR expression levels impact T cell function and response. In this thesis, I report the effects of extensive fine-tuning of CAR expression levels on the T cell transcriptome. First, I adapt microRNA silencing-mediated fine-tuners (miSFITs) technology to tune CAR expression levels in a T cell model. I leverage this model to show that tuning CAR expression correspondingly tunes CAR T cell activation. Next, I translate this technology into primary, human T cells, showing that miSFITs robustly and precisely tune CAR expression. I then demonstrate how tuned CAR expressions controls the expression of CD69 to stepwise levels. Finally, I use single-cell RNA-sequencing to comprehensively dissect the effects of tuning CAR expression in T cell responses, generating a transcriptomic atlas against step-wise levels of CAR expression. I use this atlas to first demonstrate how tuning CAR expression impacts several genes related to T cell activation, dysfunction, and memory. Using gene signatures, I demonstrate how CAR expression can be optimised to mitigate T cell dysfunction yet spare T cell activation and memory. Embarking on an unbiased discovery analysis, I identify genes, regulons, and signaling pathways that are influenced by CAR expression, providing a novel view on T cell dysfunction. My findings underscore the important role CAR expression levels have on T cell response and provide a promising avenue to address pressing, longstanding challenges hindering the success of CAR-T therapies.